2015
DOI: 10.1002/cctc.201500364
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Carbon Support on the Catalytic Activity of Ruthenium‐Magnetite Catalysts for p‐Chloronitrobenzene Hydrogenation

Abstract: Few‐layer graphene, carbon nanotubes, and N‐doped carbon nanotubes have been used to support Ru and/or Fe3O4 nanoparticles. The materials were prepared by a new single‐step sustainable method that involves: 1) a simple procedure, 2) the use of propanol as a solvent, 3) short reaction times, 4) an efficient and energy‐saving heat source, and 5) the absence of any high‐boiling‐point stabilizing agent or organic surfactant. The supported nanoparticles were characterized by TEM, XRD, inductively coupled plasma opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…Aniline was only produced when most of the 4-chloroaniline is formed. Similar work, very recently reported, showed that ruthenium–magnetite catalysts supported on carbon support leads to the formation of chloroaniline under stronger reaction conditions . As often reported in the literature, in the hydrogenation of 4-chloronitrobenzene, Pd nanoparticle-based catalysts almost lead to considerable amounts of dehalogenation product .…”
Section: Resultssupporting
confidence: 80%
“…Aniline was only produced when most of the 4-chloroaniline is formed. Similar work, very recently reported, showed that ruthenium–magnetite catalysts supported on carbon support leads to the formation of chloroaniline under stronger reaction conditions . As often reported in the literature, in the hydrogenation of 4-chloronitrobenzene, Pd nanoparticle-based catalysts almost lead to considerable amounts of dehalogenation product .…”
Section: Resultssupporting
confidence: 80%
“…Recently, MNPs have been widely used as alternative catalyst supports due to their unique properties such as simple synthesis, easy separation, high surface area, outstanding stability, convenient catalyst recycling using a simple outer magnet and prevent losing of catalyst during the separation process. Moreover, magnetic separation is a green procedure that allows time, energy, and solvents to be saved, which paves the way to the industrial application of these nanostructured catalysts …”
Section: Introductionmentioning
confidence: 99%
“…Magnetite Fe 3 O 4 NPs have received significant attention as prominent catalyst supports because of their interesting features such as chemical and thermal stability, large surface area, low cost, low toxicity, and easy separation from reaction medium with an external magnet. Moreover, magnetic separation is a green procedure that allows to save time, energy, and solvents and paves the way to the industrial application of these nanostructured catalysts . The combination of CNT–fibroin with magnetic NPs improves its properties and leads to easy catalyst separation without the need for high‐speed centrifugation, filtration, or other tedious work‐up processes.…”
Section: Introductionmentioning
confidence: 99%